Efficacy and maintenance strategies of two-compound formulation calcipotriol and betamethasone dipropionate gel (Xamiol® gel) in the treatment of scalp psoriasis: results from a study in 885 patients. (February 2014) - Saraceno, Rosita; Camplone, Germana; D'Agostino, Magda; De Simone, Clara; Di Cesare, Antonella; Filosa, Giorgio; Frascione, Pasquale; Gabellini, Massimo; Lunghi, Franco; Mazzotta, Annamaria; Peris, Ketty; Scotto Di Luzio, Genoveffa; et al.
Background: Previous studies showed the efficacy of a formulation containing calcipotriol and betamethasone dipropionate for the treatment of psoriasis. Objective: To investigate maintenance strategies of a formulation containing calcipotriol (50 µg/g) and betamethasone dipropionate (0.5 mg/g) for the treatment of scalp psoriasis. Materials and methods: Nine-hundred and four patients were screened and randomised on a 1:1 basis in two groups: maintenance of two applications per week (group A) versus on-demand therapy (group B). Clinical evaluation was performed at weeks 0, 2, 4, 8 and 12. Results: Eight-hundred and eighty-five patients were randomised: 441 in group A and 444 in group B. From week 2, both groups showed a significant clinical improvement compared with baseline; at weeks 8 and 12, group A demonstrated a higher clinical response compared with group B (p < 0.05). This difference was statistically significant (OR 0.47, 95% CI 0.37, 0.60). Conclusions: The maintenance of twice-weekly application versus on-demand treatment of calcipotriol/betamethasone dipropionate gel is more effective and is associated with a lower rate of relapse.